Using a condom to prevent cement interdigitation into bone during the first stage of a two-stage revision arthroplasty for a periprosthetic joint infection - Oosthuizen, Jannie (University of the Free State, 2018)
Introduction and Aims: Total joint replacements are a universally accepted treatment in patients with end-stage osteoarthritis, post-traumatic arthritis, inflammatory arthritis, avascular necrosis of the femoral head as well as developmental dysplasia.1,2 Due to an ageing population the demand for these procedures are increasing. On the other hand complications associated with arthroplasty will also increase. It can be argued that the most devastating complication following arthroplasty is infection. Prosthetic infections are difficult to treat and usually requires revision surgery. Whether the revision is done in a single stage or as a two-staged procedure, it remains a challenge to remove the infected prosthesis and replace it with a temporary antibiotic spacer. If the spacer is inserted as for a primary or uninfected revision replacement, interdigitation of the cement into the interstitial spaces of the bone occurs. In non-infected primary or revision surgery this is desirable as this strengthens the bone-cement-interface resulting in a stable prosthesis. Once an implant becomes infected and a two-stage revision is planned, the very same strong bone-cement interface presents a serious problem. Removal of these infected implants can be very time-consuming. If one can prevent interdigitation of the cement at the time of insertion of the temporary cement spacer, it may significantly shorten the second stage of the procedure and possibly prevent complications. The purpose of this study is to determine if the interdigitation of bone cement into bone can be prevented by using a standard, government issued male or female condom during the first stage of a two-staged revision procedure. Methodology: The study was conducted in the dissection hall of the Department of Anatomy of the Faculty of Health Sciences at the University of the Free State. Eleven cadavers were available at the time of conducting the study. Standard government issued male and female condoms were used. A cross-sectional study design was used and the data was analysed by the Department of Biostatistics at the University of the Free State. Results: Twenty-one femurs and thirteen tibias were used. In the femur, we used a male condom in eleven cases and a female condom in ten cases. The condom was intact in one case and ruptured in ten cases when a male condom was used in the femur. No interdigitation of cement was seen during visual inspection in any of these cases. When a female condom was used it was intact in seven cases and not intact in three cases and no interdigitation was also noted in any of the cases. In the tibia we used a male condom in eleven and a female condom in two cases. The male condom was intact in eight cases and it ruptured in three cases with no interdigitation of cement noted. A female condom was used in only two cases and was intact in both of these with no interdigitation of cement on visual inspection. Without exception all the condoms, male and female, ruptured at the distal end covering the tip of the prosthesis whilst the part of the condom surrounding the prosthesis proximal to tip were intact and therefore prevented interdigitation of the cement. Although interdigitation was not observed in any of the cadavers, we found a statistical significant difference between intact male and female condoms when used in the femur (P = < 0.05). There was no statistical difference between intact male and female condoms when used in the tibia (P > 0.05). There was however a statistical significant difference when the intact condoms used in the tibia were compared to the intact condoms in the femur (P < 0.05). Conclusion: Our findings suggest that either a male or a female condom may be used to prevent interdigitation of cement into the trabecular bone. Using a standard government issued female condom is easier and more reliable when compared to using a standard government issued male condom. The utilization of a condom in the femur proved to be troublesome due to various reasons. Our study furthermore indicates that it is better to use a female condom in the femur. No cement interdigitation was noted upon inspection regardless of the condom used. Recommendations: We recommend that a standard government issued female condom may be used to prevent the interdigitation of cement into the trabecular bone in both the proximal femur and proximal tibia. The use of a male condom should be reserved for use in the tibia. Despite our findings in cadaveric models, further in vivo research is necessary before the technique can be advocated as safe to use in patients. Another study investigating the sterility of the condoms that were used are currently being undertaken at the UFS.
Dissertation (M.Med. (Orthopaedic Surgery))--University of the Free State, 2018
Keywords: Revision arthroplasty; Prosthetic joint infection; Interdigitation of cement; Condom